Clinical Implications of Detectable Baseline Hepatitis C Virus-Genotype 1 NS3/4A-Protease Variants on the Efficacy of Boceprevir Combined With Peginterferon/Ribavirin. (16th September 2014) - Howe, John A.; Long, Jianmin; Black, Stuart; Chase, Robert; McMonagle, Patricia; Curry, Stephanie; Thompson, Seth; DiNubile, Mark J.; Howe, Anita Y. M.
Abstract: Background.  We analyzed the impact of pretreatment variants conferring boceprevir-resistance on sustained virologic response (SVR) rates achieved with boceprevir plus peginterferon-α/ribavirin (P/R) for hepatitis C virus (HCV)-genotype-1 infection. Methods.  NS3-protease-polymorphisms emerging coincident with virologic failure on boceprevir/P/R regimens were identified as resistance-associated variants (RAVs). Baseline samples pooled from 6 phase II or phase III clinical trials were analyzed for RAVs by population sequencing. Interferon (IFN)-responsiveness was predefined as >1 log reduction in HCV-RNA level during the initial 4-week lead-in treatment with P/R before boceprevir was added. The effective boceprevir-concentration inhibiting RAV growth by 50% (EC50 ) was determined using a replicon assay relative to the wild-type referent. Results.  Sequencing was performed in 2241 of 2353 patients (95.2%) treated with boceprevir. At baseline, RAVs were detected in 178 patients (7.9%), including 153 of 1498 genotype-1a infections (10.2%) and 25 of 742 genotype-1b infections (3.4%) (relative risk, 3.03; 95% confidence interval [CI], [2.01, 4.58]). For IFN-responders, SVR24 (SVR assessed 24 weeks after discontinuation of all study medications) rates were 78% and 76% with or without RAVs detected at baseline, respectively. For the 510 poor IFN-responders, SVR24 rates were 8 of 36 subjects (22.2% [11.7%, 38.1%]) when baseline RAVs were detected vs 174 of 474 subjects (36.7% [32.5%, 41.1%]) when baseline RAVs were not detected (relative likelihood of SVR24 [95% CI], 0.61 [0.32, 1.05]). Sustained virologic response was achieved in 7 of 8 (87.5%) IFN-nonresponders with baseline variants exhibiting ≤2-fold increased EC50 for boceprevir in a replicon assay, whereas only 1 of 15 (7%) IFN-nonresponders with baseline RAVs associated with ≥3-fold increased EC50 achieved SVR. Conclusions.  Baseline protease-variants appear to negatively impact SVR rates for boceprevir/P/R regimens only when associated with decreased boceprevir susceptibility in vitro after a poor IFN-response during the lead-in period.